A comparison of phage susceptibility testing with two liquid high-throughput methods - Parmar, Krupa; Fackler, Joseph R.; Rivas, Zuriel; Mandrekar, Jay; Greenwood-Quaintance, Kerryl E.; Patel, Robin (Frontiers in Microbiology, 2024)
Phage therapy is a promising antibacterial strategy especially given that drug resistant bacterial infections are escalating globally. Because phages are not active against all strains of a given species, phages being considered for therapeutic use would ideally be tested against bacterial isolates from individual patient prior to administration. Standardized, clinically validated phage susceptibility testing (PST) methods are needed for assessing in vitro phage activity. This study compared two high-throughput liquid-based PST assays. The first, using the Biolog Omnilog™, assessed changes in microbial respiration leading to color changes based on a tetrazolium dye. The second, Agilent BioTek Cytation 7, assessed changes in optical density. Both used 96 well microtiter plate formats. Fifty-five diverse phages with activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter baumannii and Enterococcus faecalis were studied against their respective susceptible bacterial hosts and non-susceptible controls, with susceptibility defined based on plaque assay. PST was performed by both assays in replicates, with results compared in terms of hold times (time through which bacterial growth is inhibited by phage compared to controls). Coefficients of variance and interclass correlation coefficients were used to assess inter-and intra-assay reproducibility. Based on a ≤50% coefficient of variance cutpoint, 87% of Biolog and 84% of Agilent assays were considered valid for susceptible bacteria, with 100% considered valid for non-susceptible bacteria by both systems.Using an 8-hour hold time cutpoint, 100% of results matched between the two assays. The interclass correlation coefficient showed 26% excellent agreement, 35% good agreement and 17% moderate agreement between the two assays for susceptible isolates and 100% excellent agreement for non-susceptible isolates. Overall, the assays compared provided good/fair statistical reproducibility for assessment of phage susceptibility.